Subtle aortic dissection in a patient with severe aortic regurgitation and undiagnosed bicuspid aortic valve: A case report with a literature review. Issue 9 (1st June 2021) - Sef, Davorin; Brown, Stewart; Jarral, Omar A.; Hussain, Azhar; Haslam, Elizabeth; Rajakaruna, Cha; McAloon, Christopher J.
Abstract: Background and aim of the study: A subtle aortic dissection can be challenging to detect despite the availability of multiple diagnostic modalities. Whilst rare, the inability to detect this variant of aortic dissection can lead to a dismal prognosis. We present an extremely rare case of a subtle aortic dissection with supra‐annular aortic root intimal tear and acute severe aortic regurgitation in a patient with a bicuspid aortic valve. Methods: Case report and literature review conserning subtle aortic dissection is provided. Results: Initial concerns were either aortic dissection or infective endocarditis. Despite advanced multimodality preoperative imaging, diagnosis was made intraoperatively and a Bentall procedure with a mechanical aortic valve was performed. Conclusions: Our case along with the review of current literature emphasizes that current imaging techniques may be inadequate for diagnosis of this rare variant of aortic dissection.